1999
DOI: 10.1046/j.1365-2672.1999.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of a porcine myeloperoxidase against plant pathogenic bacteria and fungi

Abstract: SO N . 1999. Porcine myeloperoxidase was evaluated for its antimicrobial activity against plant pathogenic bacteria and fungi. The results indicated that the enzyme, in the presence of a small amount of hydrogen peroxide, was effective against a broad spectrum of plant pathogens. The growth of seven bacterial species, including nine pathovars, from the genera Erwinia, Pseudomonas and Xanthomonas, was significantly inhibited by the enzyme at a concentration as low as 0·4 U ml, while 4·0 U ml −1 was lethal to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
16
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 38 publications
5
16
0
Order By: Relevance
“…The reason for different sensitivity of bacteria can be found in different transparency of the cell wall [22]. The cell wall of the gram-positive bacteria consists of peptidoglycan (mureins) and teichoic acids; the cell wall of the gram-negative cells consists of lipopolysaccharides and lipoproteins [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for different sensitivity of bacteria can be found in different transparency of the cell wall [22]. The cell wall of the gram-positive bacteria consists of peptidoglycan (mureins) and teichoic acids; the cell wall of the gram-negative cells consists of lipopolysaccharides and lipoproteins [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in an increased rate of cysticidal activity and total killing of the cyst inocula by 2 h with 3% H 2 O 2 and by 4 h with 2% H 2 O 2 . The system also enabled a sublethal H 2 O 2 concentration (1%) to produce 3-log killing within 6 h. Furthermore, this finding indicates that the previously observed in vitro activity of the peroxidase-peroxide-halide system against pathogenic viruses, bacteria, fungi, and the helminth S. mansoni can be extended to include the pathogenic protozoan Acanthamoeba (10,11,13,15,16,24,28).…”
Section: Discussionmentioning
confidence: 50%
“…The primary agent involved is hypohalous acid, which destroys cells by halogenation and oxidation of cell surface components (14,17,23,28). It has been suggested that the peroxidase-peroxidehalide system acts preferentially against pathogenic rather than nonpathogenic organisms through binding to the cell surface; the target-bound peroxidase then catalyzes halide oxidation and facilitates the disproportionation of peroxide to singlet molecular oxygen at the surface of the target microbe (1, 2, 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations